Feasibility Analysis of the Company: Fitness Center LTDA (Research, Society and Development, 2025)
This report presents the activities carried out during the supervised internship, where the student had the opportunity to apply theoretical knowledge acquired throughout the course in a practical setting, specifically in the accounting and administrative areas. The main objective was to perform activities that ensured compliance with the Supervised Internship Regulations of Unitins, using accounting software to integrate theory and practice. The activities performed included the development of the company's budget, tax planning, the legalization process of Fitness Center Ltda., configuration of accounting systems, and all events related to the personnel department. In the methodology, detailed analyses of costs, revenues, and expenses were conducted in different sectors of the company, covering industry, commerce, and services. The main results include the definition of a budget that strategically allocated resources, a tax plan that optimized the tax burden, and the complete legalization of the company, allowing access to financing and the formalization of operations. Throughout the development of these activities, it was possible to foster practical skills under the supervision of a professor, which contributed to a better understanding of accounting routines in a real work environment. It is concluded that the internship experience was enriching, providing a deep understanding of accounting and administrative processes, which are fundamental for the efficient management of a company. The knowledge acquired during the internship will serve as a foundation for the student's future professional performance in the job market.